Trypanosoma cruzi13C-labeled O-Glycan standards for mass spectrometry. (6th February 2019) - Sheikh, M Osman; Gas-Pascual, Elisabet; Glushka, John N; Bustamante, Juan M; Wells, Lance; West, Christopher M
Abstract: Trypanosoma cruzi is a protozoan parasite that causes Chagas disease, a debilitating condition that affects over 10 million humans in the American continents. In addition to its traditional mode of human entry via the "kissing bug" in endemic areas, the infection can also be spread in non-endemic countries through blood transfusion, organ transplantation, eating food contaminated with the parasites, and from mother to fetus. Previous NMR-based studies established that the parasite expresses a variety of strain-specific and developmentally-regulated O -glycans that may contribute to virulence. In this report, we describe five synthetic O -glycan analytical standards and show their potential to enable a more facile analysis of native O -glycan isomers based on mass spectrometry.